Implementation of Environmentally Based Accounting Information Systems to Support Corporate Sustainability Reporting - I Putu Raka Candra DIPTA; I Gede Fajar Adi PRADANA; I Komang Aditya NUGRAHA; I Komang Agus WIRYATAMA (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:Today's companies are required to not only pursue financial profits but also pay attention to the environmental impact of their operational activities. One of the strategic efforts in supporting sustainability is to adopt an Accounting Information System (AIS) that is oriented towards environmental aspects. This article comprehensively reviews the basic concepts, benefits, and various obstacles in implementing environmentally-based AIS to increase transparency in sustainability reporting.Methodology:The research was conducted using a literature study method by reviewing various relevant literature in the fields of environmental accounting, accounting information systems, and corporate sustainability reporting.Findings:The results of the study indicate that the integration of environmental data into AIS can improve the quality of sustainability reports, increase the level of corporate accountability, and reduce potential environmental risks in the long term. This article also presents a hypothesis that the implementation of environmental-based AIS has a significant positive impact on the quality of corporate sustainability reporting.Implication:In the final section, the article emphasizes the importance of support from management, regulatory clarity, and the development of an integrated reporting system as keys to success in implementing this system.